STEM-12. THE SMALL MOLECULE DRUG CBL0137 INCREASES THE LEVEL OF DNA DAMAGE AND THE EFFICACY OF RADIOTHERAPY FOR GLIOBLASTOMA. (12th November 2021) - Tallman, Miranda; Zalenski, Abby; Deighen, Amanda; Grubb, Treg; Schrock, Morgan; Mortach, Sherry; Kastury, Preetham; Huntoon, Kristin; Summers, Matthew; Venere, Monica
Abstract: Glioblastoma (GBM) is a fatal and incurable brain tumor, with an average life expectancy after diagnosis of only 12-15 months. A main reason for the lethality of GBM is inevitable recurrence, caused by a small population of the tumor cells, called cancer stem cells (CSCs). These cells are aggressive, infiltrative, and resistant to current GBM treatments of chemotherapy and radiotherapy. We use a small molecule drug, CBL0137, which inhibits the FACT (facilitates chromatin transcription) complex leading to cancer cell specific cytotoxicity. Here, we show that CBL0137 sensitized GBM CSCs to radiotherapy and hence lead to increased CSC death and prolonged survival in preclinical models. Clonogenic assays were used to show that CSCs were radiosensitized after CBL0137 treatment. We saw increased DNA damage when GBM CSCs were treated with CBL0137, as well as a decrease in foci resolution over time, when CBL0137 was combined with irradiation. In order to elucidate if the increase in DNA damage was directly due to the inhibition of the FACT complex, we depleted the level of FACT in our GBM CSCs. FACT depletion also led to increased DNA damage, and even more so when combined with irradiation. To validate whether combination therapy sensitized CSCs to radiotherapy in vivo, we used a subcutaneous mouse model and showed combination treatment decreased CSCs frequency in these tumors as well as decreased tumor volume. With an orthotopic model of GBM, we showed that CBL0137 treatment followed by radiotherapy significantly increased survival of mice bearing tumors over either treatment alone. Together, this work establishes a new treatment paradigm for GBM, which sensitizes radio-resistant GBM CSCs to irradiation, a critical component of patient care. Radio-sensitizing agents, including CBL0137, pose an exciting new therapeutic capable of increasing the efficacy of irradiation, by inclusively targeting CSCs.